'Natural born carers'? Reconstituting gender identity in the labour of calf care. (October 2022) - Enticott, Gareth; O'Mahony, Kieran; Shortall, Orla; Sutherland, Lee-Ann
Abstract: Environmental crises and agricultural policy reforms are key moments for the reorganisation of farming practices, which can contribute to the reconstitution of female farming roles and identities. In this paper, we consider the role of animal disease in providing an opportunity to reconstitute female farming identities, particularly emphasising female farm employees. Focusing on the careers and labour of calf rearers, the paper shows how calf rearing identities are structured and contested, and linked to cultures of care that are shaped by patriarchal farming relations. Drawing on 25 biographical interviews, the paper reveals four distinct narratives of calf rearing: natural born carers, rescue, taking back control, and from outsider to insider. Despite significant changes to the organisation of animal health and welfare for calves, these narratives reveal the marginal status of both calves and calf rearers. Calf rearers' labour of care encompasses both affectual attachments to calves but also family and farm relationships, reflecting how careful rearing is configured by the material and cultural relations of farming. Whilst some calf rearers have been able to challenge these relationships and reconstitute calf rearing identities, the narratives suggest that calf rearers lack agency to change animal health practices. Awareness of these gendered dimensions to calf rearing and animal health is vital for policy makers seeking to improve the health of livestock. Highlights: Calf rearers play an important role in managing animal health and welfare. Changes to animal health may allow calf rearing identities to be contested. Four narratives are identified revealing different calf rearing careers and experiences of care. Calf rearing is highly gendered; calf rearers lack agency to contest identities.